2021 American College of Rheumatology/Vasculitis Foundation Guideline for the Management of Polyarteritis Nodosa. Issue 8 (8th July 2021) - Chung, Sharon A.; Gorelik, Mark; Langford, Carol A.; Maz, Mehrdad; Abril, Andy; Guyatt, Gordon; Archer, Amy M.; Conn, Doyt L.; Full, Kathy A.; Grayson, Peter C.; Ibarra, Maria F.; Imundo, Lisa F.; et al.
Abstract : Objective: To provide evidence‐based recommendations and expert guidance for the management of systemic polyarteritis nodosa (PAN). Methods: Twenty‐one clinical questions regarding diagnostic testing, treatment, and management were developed in the population, intervention, comparator, and outcome (PICO) format for systemic, non–hepatitis B–related PAN. Systematic literature reviews were conducted for each PICO question. The Grading of Recommendations Assessment, Development and Evaluation methodology was used to assess the quality of evidence and formulate recommendations. Each recommendation required ≥70% consensus among the Voting Panel. Results: We present 16 recommendations and 1 ungraded position statement for PAN. Most recommendations were graded as conditional due to the paucity of evidence. These recommendations support early treatment of severe PAN with cyclophosphamide and glucocorticoids, limiting toxicity through minimizing long‐term exposure to both treatments, and the use of imaging and tissue biopsy for disease diagnosis. These recommendations endorse minimizing risk to the patient by using established therapy at disease onset and identify new areas where adjunctive therapy may be warranted. Conclusion: These recommendations provide guidance regarding diagnostic strategies, use of pharmacologic agents, and imaging for patients with PAN.